Slope Stability Analysis of Sekayu-Mangun Jaya Road STA 127+350 Reinforced with Retaining Walls - Minaka, Utari Sriwijaya; Uanza, Roby; Nisumanti, Sartika; Amalia, Ghina (Universitas Negeri Padang, 2023)
Economic growth that increases the traffic load on national roads requires these roads to have decent, safe and comfortable services. Landslide was occurred on the Sekayu-Mangun Jaya STA 127+350 road section which disrupted traffic activity. This occurrence caused the major road to shift sideways and deteriorate, rendering the route's service capacity insufficient. The road section has been repaired and is planned to use soil retaining wall reinforcement as a countermeasure. This study aims to determine the slope stability of the Sekayu-Mangun Jaya road before and after reinforcement is carried out. Slope stability analysis was performed by empirical methods using infinite slope theory and the finite element method using the Plaxis program. The calculation results show that the safety factor of the slope before the retaining wall is installed at BH-01 is 0.9. This value falls under the category of unstable slope. The safety factor at the BH-02 location was obtained at 1.3 in the moderate stability category. Slope stability after strengthening with the installation of embankments and retaining walls shows an increase in the safety factor at BH-01 to 2.59. After the slope reinforcement was carried out, the slope deformation decreased significantly to 1.5 m. The results implicated that with slope reinforcement, slope stability increases and the possibility of landslides decreases.